Design knowledge management with reconstructible structure - Koh, H; Ha, S; Kim, T; Rho, HM; Lee, SH (TECHNISCHE RUNDSCHAU EDITION COLIBRI LTD, 2003)
Critical issue in knowledge management is how to increase the adaptability of knowledge as well as how to reconstruct similar knowledge. In order to construct the design knowledge for new products, designers need to reconstruct the design knowledge with new relationships. A new design knowledge expression method, Design DNA, is proposed in this work for representing complicated relationships of design knowledge. Design DNA facilitates rearrangement of design knowledge and promotes the flexibility of knowledge structure. Design DNA is based on Layout-oriented domain knowledge and Function-oriented domain knowledge, which enables to generate new design knowledge that will result in new part geometries for given constraints on the part functions.